2021
DOI: 10.1002/ecs2.3838
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced plant leaf P and unchanged soil P stocks after a quarter century of warming in the arctic tundra

Abstract: Phosphorus (P) limits or co-limits plant and microbial life in multiple ecosystems, including the arctic tundra. Although current global carbon (C) models focus on the coupling between soil nitrogen (N) and C, ecosystem P response to climate warming may also influence the global C cycle. Permafrost soils may see enhanced or reduced P availability under climate warming through multiple mechanisms including changing litter inputs through plant community change, changing plant-microbial dynamics, altered rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 66 publications
(82 reference statements)
1
6
0
Order By: Relevance
“…Parallelly, decreased acid phosphatase activity, increased enzyme C:N, and significantly decreased MBP result in an increase in the MBN:MBP [114]. Similar findings were made in long-term warming experiments in the Arctic tundra [115], where warming led to a decrease in phosphodiesterase activity, which, in turn, led to a decrease in MBP, and the authors speculated that warming possibly enhanced microbial N or P limitation to limit enzyme production [116]. However, a 21-year warming experiment on the Tibetan Plateau has revealed that warming did not affect hydrolase activity and ratios, nor did it significantly affect MBC:MBP.…”
Section: Impact Of Global Warmingsupporting
confidence: 78%
“…Parallelly, decreased acid phosphatase activity, increased enzyme C:N, and significantly decreased MBP result in an increase in the MBN:MBP [114]. Similar findings were made in long-term warming experiments in the Arctic tundra [115], where warming led to a decrease in phosphodiesterase activity, which, in turn, led to a decrease in MBP, and the authors speculated that warming possibly enhanced microbial N or P limitation to limit enzyme production [116]. However, a 21-year warming experiment on the Tibetan Plateau has revealed that warming did not affect hydrolase activity and ratios, nor did it significantly affect MBC:MBP.…”
Section: Impact Of Global Warmingsupporting
confidence: 78%
“…Moreover, decomposition and mineralization processes are restrained due to low temperature [3,4] and poor drainage conditions [5], which limit microbial activity [6,7]. For example, in Toolik Lake, Alaska, nitrogen (N) and phosphorus (P) pools range from 22 to 133 g N m −2 and from 2 to 15 g P m −2 in tundra soils [8]. In temperate and boreal soils of eastern Canada, N pools range from 475 to 1261 g N m −2 [9], and in boreal soils, P pools range from 9 to 12 g P m −2 [10].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrolytic C‐acquiring enzymes including ÎČ‐glucosidase (ÎČ‐gluc), cellobiohydrolase (Cello), ÎČ–xylosidase (ÎČ‐xylo) and α‐glucosidase (α‐gluc); N‐acquiring enzymes including N‐acetyl‐glucosaminidase (NAG) and LAP; and P‐acquiring enzymes including phosphatase (Phos) and phosphodiesterase (PhosD) were analysed. Hydrolytic enzymes were measured using fluorescently tagged substrates and oxidative enzymes (phenol oxidase (phenol) and peroxidase (perox)) using L‐3, 4‐dihydroxyphenylalanine substrate in a slurry with soil and sodium acetate buffer adjusted to the site‐specific soil pH (6.3 for low site, 4.4 for high site) following McLaren and Buckeridge (2021).…”
Section: Methodsmentioning
confidence: 99%